Judgment in the News: The Bolsonaro Government - da Silva Rodrigues, Alex (2024)
An analysis is presented of news articles from HuffPost and Fox News of instances of judgment towards different Brazilian social actors during the presidency of Jair Messias Bolsonaro (from 2018 to 2021). The news sources were chosen to contemplate different sides of the political spectrum: HuffPost representing left-leaning views and Fox News representing right-leaning ones. Instances of judgment were classified as positive and negative. The results are interpreted in comparison to each news outlet’s alleged political slant, and a pedagogical use of this framework for the EAL classroom is proposed.